2019
DOI: 10.1249/mss.0000000000002199
|View full text |Cite
|
Sign up to set email alerts
|

Planned Aerobic Exercise Increases Energy Intake at the Preceding Meal

Abstract: Effects of exercise on subsequent energy intake are well documented, but whether pre-exercise energy intake is affected by future planned exercise is unknown. This study investigated the effect of planned late-afternoon exercise on appetite and energy intake before (breakfast and lunch) and after (evening meal/snacks) exercise. Methods: Twenty healthy, active participants (10 male; age 23 ± 5 y, BMI 23.7 ± 3.2 kg/m 2 , VO2peak 44.1 ± 5.4 ml/kg/min) completed randomised, counterbalanced exercise (EX) and restin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Meal planning often dictates what and how much we eat in advance of an eating occasion, which is likely to be influenced by how much we expect to want to eat or if we anticipate a future need (Brunstrom, 2011). If expected satiety is reduced in anticipation of a period of energy restriction, this may lead to greater portions being consumed in 'preparation', which subsequently compromises the magnitude of energy deficit that is created (Brunstrom et al 2010;Bell, Roe and Rolls, 2003), something that has recently been reported in the context of exercise (Barutcu et al 2019). Given the flexibility in dietary behaviour that is permitted by intermittent energy restriction, it is important to determine whether eating behaviour is affected before the period of energy restriction commences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meal planning often dictates what and how much we eat in advance of an eating occasion, which is likely to be influenced by how much we expect to want to eat or if we anticipate a future need (Brunstrom, 2011). If expected satiety is reduced in anticipation of a period of energy restriction, this may lead to greater portions being consumed in 'preparation', which subsequently compromises the magnitude of energy deficit that is created (Brunstrom et al 2010;Bell, Roe and Rolls, 2003), something that has recently been reported in the context of exercise (Barutcu et al 2019). Given the flexibility in dietary behaviour that is permitted by intermittent energy restriction, it is important to determine whether eating behaviour is affected before the period of energy restriction commences.…”
Section: Introductionmentioning
confidence: 99%
“…1 Three factor eating questionnaire (Stunkard and Messick, 1985)2 Estiamted via predictive equation(Mifflin et al 1990) …”
mentioning
confidence: 99%
“…This may result from an anticipatory compensatory behavior. This phenomenon can be cognitive, for example when a high-EE exercise (Barutcu, Taylor, Mcleod, Witcomb, & James, 2020) or a 24-hr severe energy restriction (James, James, & Clayton, 2020) is planned, leading subjects to increase intake at the prior meal or in the prior 24 hr, respectively, or conditioned, such as in humans omitting their habitual afternoon meal during 1 month, with a progressive increased EI at lunch (Chapelot et al, 2006). Even if we have no direct evidence in support of this hypothesis, this is consistent with the well-known superior adaptive power of anticipatory behaviors in energy homeostasis .…”
Section: Discussionmentioning
confidence: 99%
“…), these endocrine alterations with exercise do not appear to influence energy intake, at least acutely [ 9 ]. More recently, studies have started to examine eating behaviour in the pre-exercise period [ 25 27 ]. In contrast to previous work examining energy intake after aerobic exercise, Barutcu, Witcomb and James [ 26 ] reported that when a post-exercise meal is planned in advance of aerobic exercise, energy intake was ~ 24% greater than for planned rest.…”
Section: Introductionmentioning
confidence: 99%